2021
DOI: 10.51582/interconf.19-20.03.2021.033
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Metals and Radionuclides by Newest Functionalized Reagents in Liquid Media

Abstract: The conditions for the formation of metal complexes (aluminium, radionuclides) in solutions are considered. The properties of solid extractants (TVEX) and their application for the selective extraction of metals and radionuclides are discussed. The extraction of 90Sr, 90Y, 137Cs and U(VI) radionuclides from aqueous TVEX solutions impregnated with calixarenes C45 and CIP67 has been studied. The use of surfactants in combination with OAR (PA) is a typical example of the fact that the analytical capabilities of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…To understand the influence of some of the factors listed above, the theoretical investigations of 3,5-dihydroxy flavonol chelating with Be 2 + , Mg 2 + , Al 3 + , Ga 3 + , Zn 2 + , Cd 2 + , and BF 2 + ions in acetonitrile medium were performed using DFT method. [96] The analysis of the values of ΔH 0 f,298 for ML complexes showed that in the case of small ions (Be 2 + , BF 2…”
Section: Regioselectivity Of Flavonoid Complex Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the influence of some of the factors listed above, the theoretical investigations of 3,5-dihydroxy flavonol chelating with Be 2 + , Mg 2 + , Al 3 + , Ga 3 + , Zn 2 + , Cd 2 + , and BF 2 + ions in acetonitrile medium were performed using DFT method. [96] The analysis of the values of ΔH 0 f,298 for ML complexes showed that in the case of small ions (Be 2 + , BF 2…”
Section: Regioselectivity Of Flavonoid Complex Formationmentioning
confidence: 99%
“…The formation of the triphenyl borane complex is visible in absorption spectra, but in fluorescence spectra, the only band of phototautomer is always present. [96,112]…”
Section: Interplay Between the Complexation Of Flavonoids Inter-fragm...mentioning
confidence: 99%